Systemic Planning Strategy in Reading and Write Critically - Mardianto Mardianto; Syahrul Budiman; Muhammad Sanusi Nasution (Universitas Muhammadiyah Enrekang, 2022)
This study aims to provide an explanation of systemic planning strategies in critical reading and writing, the method used is a literature study research that is taken from the data. The research result is that the strategic planning process can provide useful results, including providing a framework for the development of annual budgets, planning management development tools, mechanisms to force management to think long term and tools to align managers with long term strategies. Writing Develops the Power of Initiative and Creativity In reading activities, a reader can find everything that is needed, which is available in reading. Writing Encourages Habits and Cultivates Ability to Find, Gather, and Organize Information Observations and experiences so far show that the reason people fail to write is because they do not know what they are going to write.